2008
DOI: 10.1542/peds.2007-2989
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Celiac Disease Risk Between Swedish Birth Cohorts Suggests an Opportunity for Primary Prevention

Abstract: The difference in celiac disease risk between birth cohorts at comparable ages suggests an opportunity for primary prevention. This highlights the importance of further exploring the role of infant feeding and exogenous factors besides dietary gluten that might initiate or prevent disease development. Moreover, on the basis of postepidemic incidence trends, we speculate that the Swedish epidemic might not have been as unique as thought previously, although its magnitude was striking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 30 publications
8
58
1
Order By: Relevance
“…Incidence in epoch 4 is also comparable to that reported in Finland (12.3/100 000) 20 but still much lower than that in Sweden (44/100 000). 10 Buchanan et al 21 observed a similar rise in numbers in the west of Scotland from 1995 to 2008. Therefore, we suspect that the rising trend in incidence applies to Scotland as a whole; however, we cannot be certain that this is the case in relation to classic cases.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Incidence in epoch 4 is also comparable to that reported in Finland (12.3/100 000) 20 but still much lower than that in Sweden (44/100 000). 10 Buchanan et al 21 observed a similar rise in numbers in the west of Scotland from 1995 to 2008. Therefore, we suspect that the rising trend in incidence applies to Scotland as a whole; however, we cannot be certain that this is the case in relation to classic cases.…”
Section: Discussionmentioning
confidence: 81%
“…5 Similar trends have been observed in Europe and North America over comparable time periods. [6][7][8][9][10] A number of articles also report that a greater proportion of children in more recent years are diagnosed through targeted screening and experience fewer GI symptoms. [7][8][9] However, no report has calculated the incidence of cases diagnosed over time because of a lower threshold to test or on the basis of the well-established classic presentation.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latest guidelines, gluten should be introduced into the diet of infants 4-6 months old, but no particular quantity is recommended. Studies have claimed that infant feeding practices, especially breastfeeding and timing of gluten introduction, may delay the onset of the disease or modify its symptoms (5)(6)(7)(8)(9)(10). In addition, they have suggested that breastfeeding at the time of gluten introduction can protect against celiac disease.…”
mentioning
confidence: 99%
“…During 2000-2010, the incidence rate of clinically detected cases of celiac disease in children in South-Eastern Norway has increased from 16 to 44/100.000/person-years (K. Størdal et al, unpublished observation). Sweden has experienced an epidemic with cohort effects on cumulative incidence (24). Such rapid changes cannot be explained by changes in the genetic composition of the population.…”
Section: Early Environmental Factors In Celiac Disease and Type 1 Diamentioning
confidence: 99%